ANALISIS DAMPAK PEMBANGUNAN JALAN TOL MEDAN TEBING TINGGI TERHADAP KEGIATAN JAJANAN USAHA MIKRO KECIL DAN MENENGAH DI PASAR BENGKEL - Januardin Manullang; Hottua Samosir (Jurnal Bisnis Terapan, 2019)
The workshop market has a pretty good potential for “dodol” business. Dodol has become a characteristic of this region so that the demand will remain stable. Sales of dodol, which increases every year, makes this food have a bright prospect to develop because the raw materials for its manufacture are available locally. The purpose of this research is to provide analysis and the impact of existing problems, from a phenomenon due to the opening of a high-cliff-field toll road to economic life and the selling power of snacks and food in small and medium-sized enterprises.There fore, it is not out of business due to development impacts of high-cliff-field toll road. The importance of carrying out this research was to give a solution and input from the district government as well as the North Sumatra provincial government in the management of small and medium-sized micro enterprises in the workshop market. Type of Research was Case Research (Case Study). The impact of the construction of the Medan-Tebing Tinggi toll road is very important for the MSME community around the workshop market. The impact was not only on the community but also on the regional government.Per capita income from the MSME market workshop decreased dramatically to 50% of income per month. In addition, fewer workers were employed by MSMEs, where previously they could employ 2 to 5 people per store. Now they can only employ 1 to 2 people. Regional Original Income derived from restitution has significantly dropped since the construction of the toll road. On the other hand, the positive impact felt by the market community is that there was no congestion and the air pollution decreased.